Coopération chercheurs-praticiens pour analyser l’activité et concevoir des ressources de formation - Serge Leblanc (Éducation et Socialisation)
This article looks into how researchers and practitioners cooperate in the study of human activity and its transformations. To present our way of designing and implementing our research, which constitutes an alternative to "academic" studies and/or "action" studies, we will describe (a) the merits of conducting technological research projects that are organically connected to one or more empirical research projects, (b) our view of researcher-practitioner cooperation that sees it as a route to developing and understanding human activity, and (c) the connection between activity analysis and the design process. We will provide some concrete illustrations of these three axes, based on empirical and technological studies in the course-of-action research trend, conducted in the domains of teacher education and team-driver training.